Effect of Interferon-γ Treatment on 24-Hour Variations in Plasma ACTH, Growth Hormone, Prolactin, Luteinizing Hormone and Follicle-Stimulating Hormone of Male Rats - Cano, Pilar (2005)
Interferon-gamma (IFN-gamma) is a cytokine produced by T helper cells on antigenic challenge that may affect the release of several pituitary hormones. However, in vitro or in vivo studies have yielded disparate results with stimulatory, inhibitory or absent effects of IFN on pituitary hormone release. One of the reasons for these discrepancies could be that hormone changes were commonly assessed at a single time point in the day-night cycle. In this study we measured the circadian pattern of plasma ACTH, growth hormone (GH), prolactin, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) at 6 different time points within a 24-hour cycle in adult male Wistar rats. METHODS: Groups of 6-8 rats kept under light from 08:00 to 20:00 h daily received 5 daily injections intraperitoneally of human IFN-gamma (10(5) IU/kg body weight) or saline at 08:30 h. Plasma ACTH, GH, prolactin, LH and FSH levels were measured by a homologous specific double antibody RIA. RESULTS: A factorial ANOVA for main effects indicated a significant 43% increase of circulating prolactin in IFN-gamma-treated rats. Time of day changes were significant for the five hormones examined and these diurnal variations became altered by IFN-gamma administration, with a phase advance of ACTH peak, a suppression of the rest phase peak of GH, the appearance of a second peak of prolactin at an early phase of daily photoperiod, and the blunting of the 24-hour variations of plasma FSH. CONCLUSION: The data point out an effect of IFN-gamma on the mechanisms responsible for the circadian organization of pituitary hormone release.